Evaluation of mixing conditions and its inﬂuence over free residual (2012)
We performed a real scale evaluation of mixing conditions and its inﬂuence on water quality in a compensation tank of drinking-water distribution system located in the city of Cali, Colombia. The hydrodynamic study with continuous injection of tracer, and temperature and free chlorine measurements for identifying the mixing regime in the tank’s interior, residence time, thermal stratiﬁcation, and chlorine variations in the stored water showed the typical characteristics of a compensation tank. We concluded that water recirculation, inadequate water exchange, low moment ﬂuxes associated with low velocity ﬂows, and punctual thermal stratiﬁcation could lead to high water age, high residence times in the tank, inadequate mixing, and important loss of free residual chlorine. The methodology developed is suitable for evaluation and optimization of compensation tanks of drinking water distribution systems.